ANALISIS KESESUAIAN LAHAN DI KEC. WITA PONDA DAN BUMI RAYA KAB. MOROWALI UNTUK PENGEMBANGAN PERKEBUNAN KELAPA SAWIT - Syamsul Syukur (Universitas Tadulako, 2008)
Development of agribusiness of oil palm represents one of needed steps as activity of development of plantation sub-sector in order to improve agricultural sector revitalization. Plantation of oil palm in this time has expanded not only conducted by state companies, but also by private sector and people. In general, development of agribusiness of oil palm still has a good prospect, evaluated from price, product development and exporting. Internally, agribusiness development of oil palm supported by farm availability and productivity potency have progressively improved and expanding through downstream industry. Land suitability analysis in sub district of Wita Ponda and Bumi Raya district of Morowali represent effort which in line with above mentioned opportunity. The effort aims to develop agribusiness of oil palm in rural to speed up rural economic activities, create employment, improve prosperity of society. Result of land suitability analysis gave picture that there were 3 (three) classes according to the land suitability: (i) Very suitable class which cover 75 % of total area, equal to 15.000 ha, (ii) Less suitable class which cover 15 % of total area, equal to 3.000 ha, and (iii) Non suitable class which cover 10 % of total area, equal to 2.000 ha. Thereby, the regions of sub district of Wita Ponda and Bumi Raya still have sufficient area for the development of plantation of oil palm.